ALTERNATIF STRATEGI BAURAN PEMASARAN PADA PT INDOFARMA GLOBAL MEDIKA CABANG JEMBER - Nisa, Silfiana; Sarwedi, Sarwedi; Wulandari, Deasy (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2015)
Abstract:The purpose of this study was to determine the strengths, weaknesses, opportunities, threats, and the position in the IE Matrix, Space Matrix, SWOT Matrix, as well as to find out alternative marketing strategies toward sales of PT Indofarma Global Medika Jember. Sample of the research consisted of 8 respondents. The analysis tool used was SWOT analysis. Results showed that the internal strength environment variableswere products, partnerships, pricing, and distribution channels, while the weaknesses consisted of product, human resources, and promotion. The external environment variables being the opportunities were technology, social and cultural environment, market togetherness and resources similarity, and competition among rival firms, while the threats consisted of potential entry of new competitors and the bargaining power of suppliers. The strategic position of PT Indofarma Global Medika in IE matrix was growing and developing. In the matrix space, the position was in the aggressive profile.In the SWOT matrix, the position was in the strategy of SO, WO, ST, WT interconnected. Alternative strategies of PT Indofarma Global Medika Jember branch weremarket penetration, market development, and product development. Keywords: SWOT Analysis, IE Matrix, Space Matrix, and SWOT Matrix.